Granulocytic myeloid‐derived suppressor cells (GR‐MDSC) accumulate in cord blood of preterm infants and remain elevated during the neonatal period. (26th October 2017) - Schwarz, J.; Scheckenbach, V.; Kugel, H.; Spring, B.; Pagel, J.; Härtel, C.; Pauluschke‐Fröhlich, J.; Peter, A.; Poets, C. F.; Gille, C.; Köstlin, N.
Summary: Preterm delivery is the leading cause of perinatal morbidity and mortality. Among the most important complications in preterm infants are peri‐ or postnatal infections. Myeloid‐derived suppressor cells (MDSC) are myeloid cells with suppressive activity on other immune cells. Emerging evidence suggests that granulocytic MDSC (GR‐MDSC) play a pivotal role in mediating maternal–fetal tolerance. The role of MDSC for postnatal immune‐regulation in neonates is incompletely understood. Until the present time, nothing was known about expression of MDSC in preterm infants. In the present pilot study, we quantified GR‐MDSC counts in cord blood and peripheral blood of preterm infants born between 23 + 0 and 36 + 6 weeks of gestation (WOG) during the first 3 months of life and analysed the effect of perinatal infections. We show that GR‐MDSC are increased in cord blood independent of gestational age and remain elevated in peripheral blood of preterm infants during the neonatal period. After day 28 they drop to nearly adult levels. In case of perinatal or postnatal infection, GR‐MDSC accumulate further and correlate with inflammatory markers C‐reactive protein (CRP) and white blood cell counts (WBC). Our results point towards a role of GR‐MDSC for immune‐regulation in preterm infants and render them as a potential target for cell‐based therapy of infections in these patients. Abstract : In the present study we show that numbers of GR‐MDSC are increased in peripheral blood of preterm infants during the neonatal period and afterwards decline to adult levels. In case of perinatal infection, GR‐MDSC further accumulate and correlate with inflammatory markers. These results point towards a role of GR‐MDSC for immune‐regulation in preterm infants and render them to a potential target for cell‐based therapy of neonatal sepsis.